Teachers' and students' perception of literature in ESL learning activities - Krishnan, Sujatha (2012)
Do students enjoy the activities that are carried out by their teachers in Literature in ESL (LIT in ESL) classes? There is a lot of focus from the teacher’s point of view, but the same cannot be said for the students. This purpose of this study is to investigate the Teachers’ and Students’Perceptions of Literature in ESL Learning Activities. The participants of this survey were 525 Form Four ESL students and 26 ESL teachers from four different schools in the state of Kelantan. The instruments used were questionnaires developed for teachers and students to gauge their preferences in teaching and learning related to Lit in ESL activities. The data was analysed using descriptive statistics of frequency and percentage. The findings of this study indicate that the choice of activities identified by students did not match their teachers’ choices. Students found the activities carried out as uninteresting and repetitive. The students prefer activities like drama,watching a movie and predicting a new ending to the text, while teachers, gave more reading comprehension, in class discussion and inferring. Most teachers were unaware of these students’ preference of the activities they wanted. Thus, by the matching of activities, the students would be able to not only like Literature in English, but also be more participative in class due to their interest. The disparity of preference is further discussed in terms of its pedagogical implications.